2018
DOI: 10.22146/jtbb.28765
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Corn Kernel Miso Based on Rice-koji Fermented by Aspergillus oryzae and Rhizopus oligosporus

Abstract: The suitability of corn kernel as raw material to produce miso fermented by rice-koji containing Aspergillus oryzae and Rhizopus oligosporus has been investigated. The optimization was conducted on two important factors in miso production namely mold composition in rice-koji and salt concentration. The mold composition was prepared by inoculating the spores of 2% A. oryzae, 2% R. oligosporus, and 2% the mixture of both in a ratio of 1:1, 2:1, and 1:2 (v/v) into different rice media. The mold composition was op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As with other fermented soybean foods, the characteristics of miso vary with ingredients, temperature, fermentation time, salt concentration, and the strain of A. oryzae used. It has been reported that amino acids such as glutamic acid, aspartic acid, and proline are included during the aging process of miso 18 , 19 .…”
Section: Nutrition Change Of Soybean During Fermentationmentioning
confidence: 99%
“…As with other fermented soybean foods, the characteristics of miso vary with ingredients, temperature, fermentation time, salt concentration, and the strain of A. oryzae used. It has been reported that amino acids such as glutamic acid, aspartic acid, and proline are included during the aging process of miso 18 , 19 .…”
Section: Nutrition Change Of Soybean During Fermentationmentioning
confidence: 99%